2017
DOI: 10.1111/1365-2664.13002
|View full text |Cite
|
Sign up to set email alerts
|

Novel application of explicit dynamics occupancy models to ongoing aquatic invasions

Abstract: Identification of suitable habitats, where invasive species can establish, is an important step towards controlling their spread. Accurate identification is difficult for new or slow invaders because unoccupied habitats may be suitable, given enough time for dispersal, while occupied habitats may prove to be unsuitable for establishment. To identify the suitable habitat of a recent invader, I used an explicit dynamics occupancy modelling framework to evaluate habitat covariates related to successful and failed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…A negative relationship was reported for bullfrog abundance, where higher abundances occurred closer to cities, consistent with expectations. Other studies have also reported higher invasive abundance in more disturbed environments (Riley et al, 2005; Ficetola, Thuiller & Miaud, 2007; Sepúlveda et al, 2015; Sepulveda, 2018). In contrast, crayfish abundance was significantly positively correlated with distance from cities, where lower abundances were recorded closer to cities.…”
Section: Discussionmentioning
confidence: 85%
“…A negative relationship was reported for bullfrog abundance, where higher abundances occurred closer to cities, consistent with expectations. Other studies have also reported higher invasive abundance in more disturbed environments (Riley et al, 2005; Ficetola, Thuiller & Miaud, 2007; Sepúlveda et al, 2015; Sepulveda, 2018). In contrast, crayfish abundance was significantly positively correlated with distance from cities, where lower abundances were recorded closer to cities.…”
Section: Discussionmentioning
confidence: 85%
“…sinks) but their landscape‐level persistence is maintained through some populations existing in suitable habitat and dispersing to other patches (i.e., sources) (Pulliam, 1988 ). There are few examples of how invasive species may exhibit source‐sink dynamics and include taxa such as mussels, amphibians, and fish (Bobeldyk et al., 2005 ; Dauphinais et al., 2018 ; Sepulveda, 2018 ). This has important implications for managing the spread of Hydrilla , as targeting the removal of large source populations may be a more effective strategy than attempting to control the species in numerous small, ephemeral sink populations (Sepulveda, 2018 ).…”
Section: Discussionmentioning
confidence: 99%